2009
DOI: 10.1021/es9006959
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Aerosol Yield of Isoprene in the Presence of an Organic Seed with Carbon Isotope Analysis

Abstract: We examined a new method to determine the aerosol yield of precursors of secondary organic aerosols in the presence of organic seed particles. To distinguish between the oxidation products of the compound in question and the organic seed, the compound was labeled with stable isotopes and aerosol samples were analyzed by isotope ratio mass spectrometry (IRMS). 13C labeled isoprene was obtained from isoprene emitting plants that were exposed to (13)CO2. The aerosol yield of isoprene was determined from the 13C/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Isoprene is also known to have a small but significant yield of SOA mass formation. Depending on seed aerosol, initial precursor concentration and relative NO x levels, SOA yields in the range of 1-5 % were reported in the literature (Kroll et al, 2005;Dommen et al, 2006;Kroll et al, 2006;Dommen et al, 2009). Including SOA from isoprene in calculations of the global SOA burden increases SOA by factors between 0.5 and 2 depending on scenarios used (Henze and Seinfeld, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Isoprene is also known to have a small but significant yield of SOA mass formation. Depending on seed aerosol, initial precursor concentration and relative NO x levels, SOA yields in the range of 1-5 % were reported in the literature (Kroll et al, 2005;Dommen et al, 2006;Kroll et al, 2006;Dommen et al, 2009). Including SOA from isoprene in calculations of the global SOA burden increases SOA by factors between 0.5 and 2 depending on scenarios used (Henze and Seinfeld, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, there are very few direct measurements of activity coefficients for relevant organic molecules over relevant organic mixtures. It seems reasonable to expect seemingly similar OA, such as SOA derived from different precursors, to interact in a more or less ideal fashion, and indeed isotopic labeling experiments have confirmed this [57,58]. However, mixing of less similar organics, such as relatively non-polar POA and more polar SOA, is less clear.…”
Section: à3mentioning
confidence: 98%
“…Laboratory chamber studies of SOA mass yield at OA loadings of ∼ 10 µg m −3 from isoprene have typically found low yields from O 3 (1 % Kleindienst et al, 2007) and OH (2 % at low NO x to 5 % at high NO x Kroll et al, 2006;Dommen et al, 2009;1.3 % at low NO x and neutral seed aerosol pH but rising to 29 % in the presence of acidic sulfate seed aerosol due to reactive uptake of epoxydiols of isoprene IEPOX Surratt et al, 2010). One recent chamber study on OH-initiated isoprene SOA formation focused on the fate of second-generation RO 2 radical found significantly higher yields, up to 15 % at low NO x , suggesting that omitting later-generation oxidation chemistry could be an important limitation of early chamber determinations of isoprene SOA yields.…”
Section: Introductionmentioning
confidence: 99%